Peningkatan Hasil Belajar dan Motivasi Dalam Praktek Wirausaha Menggunakan Model Project Work - Rofiq, Ainur Rofiq (Balai Diklat Keagamaan Surabaya, 2021)
This study aims to determine a learning model that can increase motivation and entrepreneurial outcomes in class XI IPS 4 MAN Sidoarjo State Madrasah Aliyah Academic Year 2019/2020 totaling 32 students. Even though the formulation of the problems in this study are, 1) How can the application of the project work model improve the learning abilities and motivation of class XI IPS-4 students to be entrepreneurial? class XI IPS-4 MAN Sidoarjo?. 3) How is the increase in student learning motivation in entrepreneurship after using the project work model of class XI IPS-4 MAN Sidoarjo? The research was carried out by a classroom action research method consisting of 2 cycles. Each cycle consists of the planning, action, observation, and reflection stages. Before cycle 1 learning was carried out conventionally and in cycles 1 and 2 learning was carried out using the Project Work model. The data used in each cycle are the results of practical tests and questionnaires about learning motivation that are distributed to all students. The results show that the Project Work learning model can increase student motivation and learning outcomes. In the application of this project work method in cycle I, the results were obtained. 88.75% and cycle II was 97.14%, meaning that the application of the project work method achieved what was expected, namely 90%. Student learning outcomes have increased. cycle I amounted to 81.25% (26 students) and in cycle II became 93.75% (30 students) This means that there is an increase from cycle I to cycle II which was obtained more than 90%. Student learning motivation has increased in cycle I with score 3.54 (happy score) and up in cycle II by 4.54 (very happy score).